2019
DOI: 10.1093/ntr/ntz076
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-Related Counseling and Documentation in Adolescent Primary Care Practice: Challenges and Opportunities

Abstract: Introduction Primary care visits present an opportunity to reduce tobacco use and tobacco smoke exposure (TSE) among adolescents. To date, few studies have examined tobacco-related electronic health record (EHR) documentation in adolescent visits. The purpose of this study was to (1) describe tobacco-related EHR documentation practices in adolescent care clinics, including whether alternative tobacco products, parental use, and TSE were addressed; and (2) identify aspects of adolescent tobacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
1
5
0
1
Order By: Relevance
“…The current study was the first step in a study to develop and test a comprehensive tobacco treatment program at this hospital. Our results align with studies of pediatric healthcare providers, which also reported similar barriers to conducting tobacco screening and counseling 14,32 . Additionally, our study had low representation of racial/ethnic minorities.…”
Section: Limitationssupporting
confidence: 89%
“…The current study was the first step in a study to develop and test a comprehensive tobacco treatment program at this hospital. Our results align with studies of pediatric healthcare providers, which also reported similar barriers to conducting tobacco screening and counseling 14,32 . Additionally, our study had low representation of racial/ethnic minorities.…”
Section: Limitationssupporting
confidence: 89%
“…Screening tools for youth EC use have not yet been developed and validated, but questions about EC use can be easily integrated into existing assessment methods [ 87 ]. The absence of electronic medical record prompts for the assessment of EC use has been identified as an area requiring attention in adolescent primary care visits [ 88 ]. Table 2 offers items to consider for assessment based on available evidence [ 1 , 19 , 87 ].…”
Section: Assessment Of Vaping In Youthmentioning
confidence: 99%
“…Birinci basamakta bireysel bilgilendirmenin erişkin dönemde tütün kullanımını engellemesine yönelik çalışmalara rastlanmamış olmakla birlikte periyodik muayeneler sırasında sigara kullanımının sorgulanması, zararları hakkında bilgilendirilmesi ve bireye tütün ürünlerini kullanıyorsa bırakması yönünde danışmanlık verilmesi aile hekimliğinin rutin bir uygulaması olarak önerilmektedir. (9)(10)(11) Tuzla EASM'de ise 18 yaş ve üzeri bireylerde sigara kullanım oranı %17,5 (n=28) iken, sigara ve tütün kullanımının zararları hakkında bilgilendirilme oranı %25,6 (n=41)'dır.…”
Section: Discussionunclassified